(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This paper addresses the need to introduce a new direction within ethnographic archaeology — musical archaeology. Collecting all findings related to instruments that produce musical sounds from across the Turkic countries could serve as the foundation for a comprehensive reconstruction of the history of music — more specifically, the history of musical instruments among Turkic peoples from ancient times to the present day. The subject of this paper is musical instruments discovered in archaeological excavations.The topic concerns the implementation of musical-ethnographic archaeology. The aim of the study is to highlight this direction in the work of ethnomusi-cologists and to articulate the core problem. The intended outcome is to organize efforts to gather materials related to archaeological finds in the fields of musical archaeology or musical ethnography. Its practical application involves collecting data from all Turkic countries to create a kind of “roadmap” of discoveries and chronological data. The conclusion emphasizes that, for the first time on an international platform, attention is being drawn to the absence of this field — and that an attempt is being made to restore historical justice regarding the musicality of the Turkic peoples and the inventiveness of their ancestors in the search for cultural and musical aesthetics.